Scaling-up agricultural innovations: Who should be targeted? - Bedi, Shaibu Mellon; Azzarri, Carlo; Kotu, Bekele Hundi; Kornher, Lukas (International Association of Agricultural Economists, 2021)
We adopt the newly redefined marginal treatment effect (MTE) framework to examine how farmers' resource endowment and unobserved factors affect the marginal benefit of adopting sustainable intensification of agricultural practices (SI practices), estimate the average and the marginal benefits of adopting the SI practices, and identify the farm households at the margin of participation that need to be targeted during scaling-up. Findings show that farmers’ unobserved factors and resource endowment influence the marginal benefit of adopting SI practices. Point estimates indicate that the adoption of SI practices increases the maize yield and net returns of adopters. Estimates further reveal that the average benefit for adopters differ from the marginal benefit for new farmers at the margin of participation. Finally, our findings suggest that not all farm households at the marginal entrants would benefit from all the potential scaling-up options, except households who by socio-economic characteristics appear least likely to adopt. We conclude that these households should be targeted to enhance adoption as well as maximize the return on investment during scaling-up of the SI practices